Civil society as political narrative concept in English-language news reports and opinion articles - Kaptiurov, Andrii (Studies in Linguistics, Culture and FLT (Online), 2025)
In the 21st century, civil society represented by non-governmental organizations and activist movements has become an influential actor, along with governments and the business sector. Mass media play an important role in shaping citizens’ awareness and attitudes towards actions initiated by activist groups, yet mass media representations of civil society have not been analyzed so far. The research approaches English-language mass media texts (news reports and opinion articles) that cover civil society and its activity as narratives and civil society as a political narrative concept. In other words, the sample of articles consists of recurring stories about a conflict in which civil society representatives confront their opponents in an attempt to eliminate a social problem with varied outcomes. The findings suggest that representations of civil society in news reports and opinion articles are complementary. News reports depict civil society by covering events straightforwardly and factually, with headlines being succinct narratives with predetermined slots and the main body adding more details. Opinion articles aim to explore social processes in depth to show their complexity: they contain several interrelated narratives on different levels (personal, local, and national